Resolution enhancement techniques in microscopy - Cremer, Christoph; Masters, Barry R. (The European physical journal. H, Historical perspectives on contemporary physics, 2013)
We survey the history of resolution enhancement techniques in microscopy and their impacton current research in biomedicine. Often these techniques are labeled superresolution, orenhanced resolution microscopy, or light-optical nanoscopy. First, we introduce thedevelopment of diffraction theory in its relation to enhanced resolution; then we explorethe foundations of resolution as expounded by the astronomers and the physicists anddescribe the conditions for which they apply. Then we elucidate Ernst Abbe’s theory ofoptical formation in the microscope, and its experimental verification and disseminationto the world wide microscope communities. Second, we describe and compare the earlytechniques that can enhance the resolution of the microscope. Third, we present thehistorical development of various techniques that substantially enhance the opticalresolution of the light microscope. These enhanced resolution techniques in their modernform constitute an active area of research with seminal applications in biology andmedicine. Our historical survey of the field of resolution enhancement uncovers manyexamples of reinvention, rediscovery, and independent invention and development of similarproposals, concepts, techniques, and instruments. Attribution of credit is thereforeconfounded by the fact that for understandable reasons authors stress the achievementsfrom their own research groups and sometimes obfuscate their contributions and the priorart of others. In some cases, attribution of credit is also made more complex by the factthat long term developments are difficult to allocate to a specific individual because ofthe many mutual connections often existing between sometimes fiercely competing, sometimesstrongly collaborating groups. Since applications in biology and medicine have been amajor driving force in the development of resolution enhancing approaches, we focus on thecontribution of enhanced resolution to these fields.
Gesehen am 28.05.2021